Polymeric composites with rice hulls : an introduction - Defonseka, Chris (De Gruyter, 2019)
Polymeric composites with rice hulls have superior properties compared with other polymer composites and are suitable for a wider range of applications. This book explains what it is that makes polymeric composites with rice hulls ideal substitutes for natural wood and how they may help ease global environmental concerns. It is an ideal source of information for researchers, resin-pellet manufacturers, processors and end users.- Resumé vydavatel
Keywords: polymerní kompozitní materiály; plniva; rýže; polymer composite materials; fillers (materials); rice; elektronické knihy; monografie; electronic books; monographs